Alterations in Distribution of Blood Flow to the Lung's Diffusion Surfaces During Exercise - Cross, Carroll E. (1973)
We measured simultaneously, by single breath methods, pulmonary capillary blood flow (Q̇(c)), carbon monoxide diffusing capacity (DL(CO)), and isotopic oxygen ((18)O(18)O) diffusing capacity (DL(18)(O(2))) in five normal males during conditions of rest and moderate exercise at mixed venous O(2) tensions (PO(2) 33-44 mm Hg). During moderate exercise at a work load of 100 W. pulmonary capillary blood flow increased from 6.9±1.5 to 12.9±3.4 min(-1) and DL(18)(O(2)) increased from 25±4 to 43±3 ml·min(-1)·mm Hg(-1), whereas DL(CO) showed no significant change (45±5 to 49±10 ml·min(-1)·mm Hg(-1)). DL(18)(O(2)) increased proportionally to Q̇(c) (r = 0.74), where DL(CO) did not (r = 0.08). The greater increase in DL(18)(O(2)) during exercise can be explained by a more homogeneous diffusion/perfusion (DL(O(2))/Q̇(c)) distribution in the individual respiratory exchange units during exercise. This improved distribution of DL(O(2))/Q̇(c) acts to help prevent an increase in alveolar-arterial O(2) tension difference from developing despite the decrease in pulmonary erythrocyte transit times that occur during exercise. The insignificant rise in DL(CO) with exercise under these hypoxic breathholding conditions may result from pulmonary vasomotor responses to short-term hypoxia or from relative insensitivity of DL(CO) to moderate levels of exercise.